answersLogoWhite

0


Best Answer

The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.

User Avatar

Wiki User

โˆ™ 2014-05-29 23:52:03
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the sum of 3x plus 2 and -4 plus 3?
Write your answer...
Submit
Related questions

Find the sum of the roots x2 plus 3x equals -2?

-3/2


What must be added to 5 x squred plus 6x plus 9 so that the sum is negative x squered plus 3x plus 3?

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6


What is (6(3x2) plus 8x-3) plus (3(3x2)-7x plus 2) simplified?

The sum 6 (3x^2) + 8x -3 plus 3 (3x^2) - 7x + 2 = 27 x^2 + x -1


What is the trinomial (3x plus 9)(3x plus 2)?

9x+3


Find the sum 3x2 plus 2x plus 3 plus x2 plus x plus 1?

3x2 + 2x + 3 + x2 + x + 1 = 4x 2+ 3x + 4


What is the answer to (3x plus 3)(x plus 4)?

It is: 3x^2 +15x +12


What is parenthesis 4x to the second power plus 3 in parenthesis plus parenthesis 3x to the second power plus 8 in parenthesis?

(4x ^2 + 3) + (3x ^2 + 8) = ( 4x^2 + 3x^2 ) + (3+8) = 7x^2 + 11


What is x if 3x plus 2 plus 3x-4 equals 44?

x = 7 and 2/3


2x 4 - 6x 3 plus 5x 2 - 3x plus 2 x - 2?

2(3x + 4) + 5x - 2


What is the simplification of the expression 3x plus 4y plus 2 plus 6y plus 3?

It is: 3x+10y+5 simplified


What is the sum of the constant terms in the expression -5-5x plus 3-3x-10x plus 1?

-1


What is 3(x plus 2) plus 5?

It is equivalent to: 3x+6+5 = 3x+11


What is x3 plus ax plus 3a plus 3x2?

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)


How do you fine 5x plus 3 plus 3x?

You can add the x's together, which gives 8x+3. There is nothing else that can be done with that sum.


What is the answer to 3x plus 2 equals 0?

3x + 2 = 0 3x = -2 x = -2/3


How do you solve the equation 3x-2 equals 2x plus 3?

3x-2 = 2x+3 3x-2x = 3+2 x = 5


Factor 3x squared plus 3x minus 60?

3x^2+3x-60=3(x^2+x+20)=3(x+5)(x-4)


3x plus 5 plus 2x-3?

5x+2.


What is the solution of 2x plus 3 equals 3x plus 5?

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2


What is the average of 3x plus 1 and x-3?

Average = (sum of the items) / (number of items)Sum of the items = (3x + 1) + (x - 3) = 4x - 2Number of items = 2Average = (2x - 1)


Factor x3 plus 2x2 plus 3x plus 6?

x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)


How do you factor -9x3-3x2 plus 3x plus 1?

If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)


The sum of a number plus 3 is squared is 11 more than the sum of the number plus 2 when squared What is the number?

When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.


When the sum of a number plus 3 is squared it is 9 more than the sum of the number plus 2 when squared-?

The sum of a number plus 3 to the square root of 9 to the sum of 2 would equal -2. This is a math problem.


Solve the equation for x 6x plus 6 equals 3x - 2?

6x + 6 = 3x - 2 Bring 3x to the left and subtract: 6x - 3x = 3x 3x + 6 = -2 -2 - 6 = -8 -8 / 3 X = -8/3

Study guides

๐Ÿ““
Create a Study Guide